Executive function deficits in mild cognitive impairment: evidence from saccade tasks. - Chehrehnegar, Negin; Shati, Mohsen; Esmaeili, Mahdieh; Foroughan, Mahshid (Aging & Mental Health, 2022)
Early detection of mild cognitive impairment (MCI) is necessary to prevent irreversible brain damage caused by incipient Alzheimer's disease. It has been showing that amnestic MCI (a-MCI) subjects exhibit subtle deficits in executive function that can be tested using saccade eye movements. Eye-tracking technology is a sensitive method to measure cognitive impairments in dementia and MCI. In this study, we used eye-tracking technology to explore saccade impairments to distinguish between a-MCI and the variants of reference controls. 21 patients with AD, 40 patients with a-MCI, and 59 normal participants were recruited in current study. We measured saccade reaction time, saccade errors, saccade omission, and uncorrected saccades using anti-saccade and pro-saccade tasks with 'gap' and 'overlap' procedures. These parameters were used as markers of executive function and visual attention deficits.Results: The findings revealed that more errors, more omissions, and fewer corrections characterized the saccade behavior of the a-MCI group compared to the reference group. These eye-tracking characteristics can be considered as inhibitory control and working memory deficits in a-MCI subjects. Our results thus demonstrate the applicability of the anti-saccade task as a cognitive marker in a-MCI. The work provides further support for eye-tracking as a useful diagnostic biomarker in the assessment of executive function in aging with cognitive impairments.